Metabarcoding of soil environmental DNA to estimate plant diversity globally - Vasar, Martti; Davison, John; Moora, Mari; Sepp, Siim-Kaarel; Anslan, Sten; Al-Quraishy, Saleh; Bahram, Mohammad; Bueno, C. Guillermo; Cantero, Juan José; Fabiano, Ezequiel Chimbioputo; Decocq, Guillaume; Drenkhan, Rein; et al. (Frontiers in Plant Science, 2023)
Traditional approaches to collecting large-scale biodiversity data pose huge logistical and technical challenges. We assessed how a comparatively simple method based on sequencing a short fragment (P6 loop) of the chloroplast trnL intron from soil environmental DNA (eDNA) characterises global variation in plant diversity and community composition compared with data derived from traditional plant inventory methods. Large-scale plant diversity and community composition patterns revealed by sequencing eDNA from 325 globally distributed soil samples were broadly in accordance with those derived from sources based on empirical (GBIF) or extrapolated plant distribution and diversity data. The success of the eDNA taxonomy assignment, and the overlap of taxon lists between eDNA and GBIF, was greatest at moderate to high latitudes of the northern hemisphere. On average, around half (mean: 51.5% SD 17.6) of local GBIF records were represented in eDNA databases at the species level, depending on the geographic region. Important experimental considerations for plant eDNA studies include using a sampling volume and design to maximise the number of taxa detected and optimising the sequencing depth. However, increasing the coverage of reference sequence databases would yield the most significant improvements in the accuracy of taxonomic assignments made using the P6 loop of the trnL region.